Lestár Gyulaffi’s Manuscripts and the Fragmentation of a Magnum Opus - Bibor, Máté János (Folia Toruniensia, 2021)
Lestár Gyulaffi (1556–1606?) was a secretary of the Greater Chancery of the Transylvanian Principality. Today, he is best-known as a writer of historical notes and commentaries. These records are considered an excellent source and therefore used by scholars researching the age. As the texts have not been recently published, researchers usually use the 19th-century text edition. However, looking at the original documents preserved in the ELTE University Library in Budapest, one realizes that Gyulaffi’s writings do not form a compact work, the 19th-century edition is largely a constructed text. In the present paper I will present what additional information can be obtained from the examination of the manuscripts.